Increased risk of adverse drug reactions by higher linezolid dose per weight in multidrug-resistant tuberculosis - Kuhlin, Johanna; Davies Forsman, Lina; Osman, Aisha; Skagerberg, Magdalena; Jonsson, Jerker; Groenheit, Ramona; Mansjö, Mikael; Werngren, Jim; Alffenaar, Jan-Willem; Schön, Thomas; Bruchfeld, Judith (International journal of antimicrobial agents, 2024)
Linezolid treatment has a high risk of toxicity and adverse drug reactions (ADR) are frequent. Few studies have investigated risk factors of major ADRs separately, therefore, we aimed to evaluate major ADRs including peripheral neuropathy in relation to risk factors and drug concentration levels of linezolid in a high-resource setting for multidrug-resistant tuberculosis (MDR-TB). We conducted a retrospective cohort study including participants treated with a linezolid-containing MDR-TB regimen in Sweden 1992–2018. Data was collected from medical records. ADRs were classified according to Common Terminology Criteria for Adverse Events (version 5.0). Of all participants (n = 132), 43.2% were female and the median age 28 y. The median linezolid treatment was 6.5 months (IQR 3.0–12.7) with a median daily dose of 9.6 mg/kg/d. Any ADR was seen in 58.3% (n = 77) of participants, with 35.6% having peripheral neuropathy (n = 47), 27.3% anaemia (n = 36), 22.0% leukopenia (n = 36) while 6.1% (n = 8) had optic neuritis. The median time for peripheral neuropathy was 3.6 months (IQR 2.1–5.9) and 8.3 months (6.2–10.7) for optic neuritis. A >2.0 mg/L trough concentration (n = 40) was associated with anaemia (P = 0.0038) and thrombocytopenia (P = 0.009) but not with peripheral neuropathy. In multivariable analysis, a dose ≥12 mg/kg/d was associated with time to peripheral neuropathy (HR 2.89, 95% CI 1.08–7.74, P = 0.035), anaemia (HR 6.62, 95% CI 2.22–19.8, P = 0.001) and leukopenia (HR 5.23, 95% CI 1.48–18.5, P = 0.010). Linezolid ADRs were frequent in a high-resource setting. Structured, regular follow-up for ADRs and adjusting dosing according to body weight followed-up by monitoring of drug concentrations early may reduce toxicity. [Display omitted]